2018
DOI: 10.1061/(asce)co.1943-7862.0001542
|View full text |Cite
|
Sign up to set email alerts
|

Viability of the BIM Manager Enduring as a Distinct Role: Association Rule Mining of Job Advertisements

Abstract: Abstract:Building Information Modeling (BIM) has developed as the definitive technology for managing construction projects. With its rise, the corresponding role of BIM manager has emerged as a necessary adjunct role in coordinating BIM enabled projects. The ascent of the BIM manager has attracted a significant body of research investigating the various competencies and responsibilities required of the role. While BIM is here to stay, the work of Akintola et al. (2017), however, asserts that a distinct role or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 37 publications
4
34
0
1
Order By: Relevance
“…The role of the BIM actor clearly shows a tension in that, on the one hand, they are involved in processes of cocreation in developing new practices, competing against existing practices as well as existing roles, and, on the other hand, they constantly negotiate their particular tasks and responsibility, as well as their role. In our observations we found that the BIM role can infringe on the role of the project manager, which is in line with earlier work of Akintola et al (2017) and Hosseini et al (2018) who discuss the overlap of the BIM role with the role of the project manager and that the role might disappear when the project manager obtains more BIM skills.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The role of the BIM actor clearly shows a tension in that, on the one hand, they are involved in processes of cocreation in developing new practices, competing against existing practices as well as existing roles, and, on the other hand, they constantly negotiate their particular tasks and responsibility, as well as their role. In our observations we found that the BIM role can infringe on the role of the project manager, which is in line with earlier work of Akintola et al (2017) and Hosseini et al (2018) who discuss the overlap of the BIM role with the role of the project manager and that the role might disappear when the project manager obtains more BIM skills.…”
Section: Discussionsupporting
confidence: 92%
“…A number of recent studies have discussed various BIM roles (Akintola et al 2017;Davies et al 2017;Uhm et al 2017;Hosseini et al 2018;Jacobsson and Merschbrock 2018;Bosch-Sijtsema et al 2019). While some of these studies make a clear distinction between different types of roles like BIM managers, BIM coordinators and BIM modellers (Davies et al 2017), others stated that the difference between BIM managers and BIM coordinators is fuzzy and that the roles perform similar duties (Hosseini et al 2018;Bosch-Sijtsema et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations